Pendidikan Formal Sebagai Pelestari Tata-Nilai dan Pembaru Kebudayaan - Ali Rohmad (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2014)
In the Islamic perspective, receptive functions that must be carried by each unit of formal education can be identified with the task of developing of habl min Allāh (حبل من الله) the fabric of human relationship with God, is also the duty of man as a servant of God (عبدالله) the human self servitude to Allah; being directive functions that must be carried by each educational unit can be identified with the task of developing of habl min al-Nas (حبل من الناس) the fabric of the relationship between humans and their universe, is also the duty of man as caliph of God on earth (خليفة الله فى الأرض) that prosperity world.